The Influence of Meaningful Work and Organizational Citizenship Behavior on Job Performance of Employees in PT X Mojokerto - Safitri, Dian; Sulistiyorini, Diyah (KnE Social Sciences, 2022)
Level of performance in a particular job is crucial because it can make a major contribution to the sustainability of the company. The purpose of this research was to examine how meaningful work and organizational citizenship behavior influence employee performance. This research used a quantitative approach and data were collected using the Individual Work Performance Questionnaire, Organizational Citizenship Behavior, and Work and Meaning Inventory. The sample of this research included 86 employees who worked at PT. X in Mojokerto who were recruited using simple random sampling. The analysis techniques used in this research were the instrument test, descriptive test and classical assumption test. The results revealed that meaningful work had no significant effect on performance (p = 0.77 > 0.05). However, the results showed that organizational citizenship behavior had a significant influence on performance (p < 0.05). The findings on the simultaneous effect of meaningful work and organizational citizenship behavior on performance revealed significant results (p < 0.05). It is recommended that future studies examine other variables that may play a role in improving performance, such as job satisfaction and leadership. Keywords: job performance, organizational citizenship behavior, meaningful work